2022
DOI: 10.1002/jha2.550
|View full text |Cite
|
Sign up to set email alerts
|

De‐escalation or discontinuation of tyrosine kinase inhibitor in patients with chronic myeloid leukemia: A multicentral, open‐label, prospective trial in China

Abstract: Background: Long-term treatment-free remission (TFR) represents a new goal for chronic myeloid leukemia (CML). Optimizing dose of tyrosine kinase inhibitors (TKIs) in the CML treatment maybe a new challenge to maintain effective and improving patients' quality of life. We hypothesized that administration of low-dose TKIs does not compromise major molecular response (MMR) in patients with CML who have a deep molecular response (DMR). Methods:We did an open-label, randomized trial at eight hospitals in China. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The molecular recurrence-free survival was lower in the discontinued group compared to the dose de-escalation group (59.9 versus 88.3) p= 0.0002. In the 12 months of dose de-escalation, 8% of patients lost MMR ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular recurrence-free survival was lower in the discontinued group compared to the dose de-escalation group (59.9 versus 88.3) p= 0.0002. In the 12 months of dose de-escalation, 8% of patients lost MMR ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The duration of previous treatment, the depth of molecular response, previous resistance, type of BCR::ABL1 transcripts, halving time, and lymphocyte subtypes are known predictive factors of molecular recurrence after tyrosine kinase inhibitors (TKI) discontinuation (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Few studies investigated the kinetics of BCR::ABL1 transcripts during a dose de-escalation phase before discontinuation in predicting molecular relapse (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Other discontinuation trials analyzed the immunological profile of CML patients by flow cytometry. Recently, Luo et al 15 showed that NK cells were increased at baseline in CML patients who did not relapse after stopping TKI compared to relapsing patients, but they did not analyze DP T cells. Irani et al also reported that patients who had a successful TFR had a higher proportion of NK cells at TKI discontinuation, but they did not evaluate the role of DP T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that low-dose TKI treatment is effective in maintaining major molecular response (MMR) ( Rea et al, 2017a ; Clark et al, 2017 ; Claudiani et al, 2021 ). Moreover, dose-halving therapy yields higher molecular recurrence-free survival rate compared to direct TKI discontinuation ( Luo et al, 2022 ). Our recent study also confirmed the feasibility of TKI dose reduction therapy for Chinese CML patients ( Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%